A podcast on urban ruins, or the aural weaving of theory and field - Paiva, Daniel (2019)
Making a podcast can be a way to weave together concepts, theories or mere thoughts about places, and the aural sensory experience of being in place. In this short article, we present the NoVOID podcast, an audio podcast on ruins and vacant lands that combines interviews with scholars from various fields of knowledge and field recordings in various sites related to the subjects of the interviews. We discuss four possibilities for generating more-than-representational knowledge that podcasts allow, namely, grounding abstract concepts or theories into the materiality of space, augmenting the knowledge conveyed in discourse through aesthetic features, assembling together different realities into a fluid experience and mitigating the power of the discourse of experts. We expect to contribute towards a growing range of creative possibilities for conveying the affective contents of geographic research that are not easily translatable into words in a text.